2008
DOI: 10.1111/j.1466-7657.2007.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in hospital nurses: a comparison of internal, surgery, psychiatry and burns wards

Abstract: Different clinical working environments appear to have an impact on the development of nurses' burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
4
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 22 publications
6
75
4
6
Order By: Relevance
“…In addition, nurses who work a regular shift in this study were usually on the morning shift. This finding is in agreement with those of Jamal and Baba (37), Glazer (38), and Krausz and Koslowsky (39) and in contrast to the study of Sahraian et al (40), who reported that nurses with regular schedules have more burnout than nurses on ro- tating shifts. The discrepancy between the results can be explained in terms of differences in workplaces.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, nurses who work a regular shift in this study were usually on the morning shift. This finding is in agreement with those of Jamal and Baba (37), Glazer (38), and Krausz and Koslowsky (39) and in contrast to the study of Sahraian et al (40), who reported that nurses with regular schedules have more burnout than nurses on ro- tating shifts. The discrepancy between the results can be explained in terms of differences in workplaces.…”
Section: Discussioncontrasting
confidence: 54%
“…Studies have shown that occupational stress is associated with minor psychiatric disorders. Issues such as the rate of absenteeism, abuse of substance and drugs, apathy and loss of motivation are higher in workers than others, and therefore, affect their occupational satisfaction and mental health (3). Dissatisfaction, work overload, lack of time, and physical stress are factors that directly affect the mental health of the individual (4).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [28] pointed out that cultural factors may have influenced the levels of burnout reported by nurses in the study. Such cultural influences are well documented by other researchers [29,30] and include factors such as gender role expectations, religion, role of the family and health care systems. Burnout has been 3 The Study…”
Section: Introductionmentioning
confidence: 93%